Future of Securitisation, Is Securitisation Dead? It's impact and Influence on the Banking Sector? - Singh, Nitish (2008)
This dissertation investigates the various aspects of securitisation, aiming to give a comprehensive understanding of the issues evolving around it. The study here focuses on the advantages and adisadvantages of securitisation, which according to some has been the root cause or at the core of the current global financial turmoil. Asset backed securitisation originated in the US in 1968 and subsequently attracted European countries to embrace it. Ever since has seen an unprecedented growth in its usage. Realising the potential, many institutions adopted the securitisation as a model, however now many institutions have now found their fingers burnt in the very process which was yielding high returns. The purpose of this report is also to analyse and reflect upon the future of securitisation and aspects of how the financial institutions, especially the banking sector would evolve in the medium to long term.